2012
DOI: 10.3171/2012.2.focus121
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of confirmatory techniques for the placement of lumbar pedicle screws

Abstract: Object There is considerable variation in the use of adjunctive technologies to confirm pedicle screw placement. Although there is literature to support the use of both neurophysiological monitoring and isocentric fluoroscopy to confirm pedicle screw positioning, there are no studies examining the cost-effectiveness of these technologies. This study compares the cost-effectiveness and efficacy of isocentric O-arm fluoroscopy, neurophysiological monitoring, and postop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 32 publications
3
14
0
1
Order By: Relevance
“…For the operative staff, the exposure is nearly zero because the whole surgical team leaves the operation room during the CT scan. Regarding the cost, Sanborn et al [27] reported that using the O-arm for confirming pedicle screw placement was the most cost-effective strategy compared to neurophysiological monitoring and isocentric fluoroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…For the operative staff, the exposure is nearly zero because the whole surgical team leaves the operation room during the CT scan. Regarding the cost, Sanborn et al [27] reported that using the O-arm for confirming pedicle screw placement was the most cost-effective strategy compared to neurophysiological monitoring and isocentric fluoroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…35 However, a recent study by Sanborn et al 43 directly compared the cost effectiveness of O-arm intraoperative neuromonitoring and postoperative CT imaging for the pedicle screw accuracy assessment in patients undergoing at least 3-level lumbar fusions. The calculations were based on 2011 Medicare reimbursement rates, and because the surgical and hospital charges were constant, they were not included in the calculations.…”
Section: 64561mentioning
confidence: 99%
“…The authors concluded that the least costly alternative was also the most effective. 43 Furthermore, if according to Hodges et al, an estimated 1% of patients would require pedicle screw revision, the nationwide annual cost was approximated to reach $40,595,000, not considering the costs associated with morbidity.…”
Section: 64561mentioning
confidence: 99%
“…Currently, the two most frequently used methods to place pedicle screws are (i) via visualization by the surgeon and (ii) via intraoperative CT-guided screw placement 20, 21 . For the former, intraoperative X-Ray confirms screw placement, whereas the latter technique allows for real-time visualization of screw placement without the need for X-Ray imaging.…”
Section: Virtual Reality Training Modulesmentioning
confidence: 99%